Ways of involving central bank in supporting economic growth - Adina Criste (Financial Studies, 2019)
Addressing the relationship between the policy of a central bank and economic growth in the post-crisis stage, the article aims to identify essential tools that the monetary authority has theoretically available to support a sustainable economic growth, in the future. In the context of the global economy developments and the challenges that it is subject to, on the one hand, and considering certain attributes of a central bank, on the other hand, there are highlighted some elements that lead us to clarify the proposed objective.
Keywords: E44; E58; F43; 330; central bank policy; communication tool; postcrisis time; financial stability